TEKNIK ANALISIS KONSUMSI ARUS LISTRIK PADA MOBIL MULTI PURPOSE VEHICLE - Hendra Firdaus; Endang Rustendi; Ade Herdiana (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
The car is not only limited to the engine, but also related to the electrical system to carry out its functions. Electricity is needed for the combustion process in cars. To store the source of electrical energy required Accu. The current that comes from the battery is direct current or DC (Alternating Current) voltage of 12 Volts. Battery functions include; When the engine is off, the battery functions as a source of electric power that functions to turn on the electrical system in the vehicle, such as turn signal lights (turn signals), horns (horns), indicators on the dashboard, city lights, head lights and so on. . When the engine is still not running, the Accu is the only source of electricity that is used, because at this time the alternator on the vehicle is not functioning. When starting using an electric starter, the battery is also the only source of electricity used to start or run the starter motor. When the engine is running, the alternator on the vehicle is functioning, so the battery is no longer the main source of electrical energy. However, when the engine is running, the battery still has a function, namely as a voltage stabilizer from the alternator. Considering the work of the alternator is less stable and depends on the rotation of the alternator, even though the alternator is equipped with a regulator but still requires a battery as a voltage stabilizer, the voltage is supplied to the electrical system in the vehicle. In Indonesia, a car with an average number of passengers capable of carrying 6 to 7 passengers is a type of MPV which stands for Multi Purpose Vehicle. The research was conducted on one type of MVP car, namely the Avanza brand car. The main power source used in the Toyota Avanza is the 12 Volt 32 Ah Accu. From the results of measurements and calculations on car electricity, it can be concluded that with the main power source Accu 12V/32Ah being able to provide Electric Current needs to all loads with a total current of 102.5 A for 0,31h before the battery is empty again.